Lentinan protects against pancreatic β‐cell failure in chronic ethanol consumption‐induced diabetic mice via enhancing β‐cell antioxidant capacity. Issue 13 (9th April 2021) - Wu, Tijun; Wang, Jiahui; Zhang, Yaru; Shao, Yixue; Li, Xirui; Guo, Yuqing; Dong, Wenyu; Wang, Lin; Chen, Fang; Han, Xiao
Abstract: Chronic ethanol consumption is a well‐established independent risk factor for type 2 diabetes mellitus (T2DM). Recently, increasing studies have confirmed that excessive heavy ethanol exerts direct harmful effect on pancreatic β‐cell mass and function, which may be a mechanism of pancreatic β‐cell failure in T2DM. In this study, we evaluated the effect of Lentinan (LNT), an active ingredient purified from the bodies of Lentinus edodes, on pancreatic β‐cell apoptosis and dysfunction caused by ethanol and the possible mechanisms implicated. Functional studies reveal that LNT attenuates chronic ethanol consumption‐induced impaired glucose metabolism in vivo. In addition, LNT ameliorates chronic ethanol consumption‐induced β‐cell dysfunction, which is characterized by reduced insulin synthesis, defected insulin secretion and increased cell apoptosis. Furthermore, mechanistic assays suggest that LNT enhances β‐cell antioxidant capacity and ameliorates ethanol‐induced oxidative stress by activating Nrf‐2 antioxidant pathway. Our results demonstrated that LNT prevents ethanol‐induced pancreatic β‐cell dysfunction and apoptosis, and therefore may be a potential pharmacological agent for preventing pancreatic β‐cell failure associated with T2DM and stress‐induced diabetes.